Accuracy of Lung Ultrasonography for Diagnosis of Heart Failure; a Systematic Review and Meta-analysis - Erfan Rahmani; Masoud Farrokhi; Mehrdad Farrokhi; Shadi Nouri; Atousa Moghadam Fard; Behnam Hoorshad; Ramin Atighi; Erfan Ghadirzadeh; Michael Tajik; Habibollah Afshang; Aida Naseri; Mohadeseh Asoudehfard; et al. (Archives of Academic Emergency Medicine)
Introduction: Despite the evident impact of ultrasonography on diagnosis in acute care settings, there is still a great deal of uncertainty regarding its accuracy. This study aimed to assess the diagnostic performance of lung ultrasonography (LUS) for the identification of acute heart failure in patients with suggestive manifestations.